Etnobotani Tumbuhan dalam Upacara Pernikahan Etnis Karo di Kecamatan Biru-Biru - Ginting, Dian Vera Br; Nasution, Jamilah; Riyanto, Riyanto; Karim, Abdul (Universitas Medan Area, 2023)
The Karo Indigenous Ceremony is a traditional ritual passed down through generations in the community. This ceremony encompasses various rituals, with a wide variety of plant species being used, each serving specific functions in accordance with ancestral teachings. This research aims to identify the plant species employed in the Karo ethnic wedding ceremony. The research methodology adopted is qualitative descriptive, utilizing interview techniques and informant selection through purposive sampling. The study's findings reveal the use of 31 plant species from 17 plant families in the Karo ethnic wedding ceremony. Plant organs used include fruits (32%), leaves (29%), rhizomes (12%), tubers (9%), stems (6%), flowers (6%), and seeds (6%).